Polymorphisms of Leptin (-2548 G/A) and Leptin Receptor (Q223R) Genes in Iranian Women with Breast Cancer - Reza Mahmoudi; Bahareh Noori Alavicheh; Mohammad Amin Nazer Mozaffari; Mohammad Fararouei; Mohsen Nikseresht (International Journal of Genomics)
Recent studies have shown that polymorphisms in leptin and leptin receptor genes are associated with increased risk for breast cancer. This study aimed at investigating -2548 G/A polymorphism in leptin gene and Q223R polymorphism in leptin receptor gene in patients with breast cancer. The study included 45 women with breast cancer and 41 healthy women. PCR-RFLP was used to determine the genotype of the subjects in terms of -2548 G/A polymorphism in leptin gene and Q223R polymorphism in leptin receptor gene. Serum levels of leptin were also measured by ELISA. For -2548 G/A polymorphism, the genotypes were homozygous AA (OR = 1.13; p=0.8) and heterozygous GA (OR = 0.41; p=0.2) and for Q223R polymorphism, the genotypes were homozygous RR (OR = 6.7; p=0.09) and heterozygous QR (OR = 8.3; p=0.06). The mean serum level of leptin was 33.22 ± 21.35 ng/mL in patients and 29.49 ± 23.27 ng/mL in the normal participants (p=0.3). Although, despite the magnitude of the associations, the results suggested no statistically significant contribution of -2548 G/A polymorphism (in leptin gene), Q223R polymorphism (in leptin receptor gene), and serum leptin levels in predicting the risk of breast cancer, further studies with larger sample size are suggested.